Multichannel information-seeking intentions in the context of public health crises - Qi, Shenghao; Tham, Jen-Sern; Waheed, Moniza; Hashim, Norliana (International Journal of Asian Social Science, 2025)
This study addresses the challenges of meeting the Chinese public’s information needs and effectively communicating risks during recurring large-scale public health crises. Drawing on a revised Risk Information Seeking and Processing (RISP) model, this study examines multichannel information-seeking behaviors. Data were collected via an online survey of 2,604 valid responses from diverse regions and genders across China. Seven hypotheses were tested using structural equation modeling. Results show that negative emotions significantly influence public responses to health crises. As perceived risk increases, negative emotions intensify while positive emotions decline. Negative emotions are linked to stronger feelings of information insufficiency, whereas positive emotions reduce such perceptions. Social expectations further heighten the sense of information inadequacy, prompting individuals to seek information through multiple channels, including interpersonal sources, traditional media, search engines, and social media. Emotions and social pressures play critical roles in shaping information-seeking behavior during public health crises, emphasizing the need for nuanced, multichannel communication strategies. This framework offers valuable insights for policymakers, health professionals, and crisis communicators aiming to design effective risk communication strategies tailored to diverse information needs and emotional responses.